Measles incidence and reporting trends in Germany, 2007–2011 - Anja Takla; Ole Wichmann; Thorsten Rieck; Dorothea Matysiak-Klose (Bulletin of the World Health Organization, 2014)
Objective We aimed to quantify progress towards measles elimination in Germany from 2007 to 2011 and to estimate any potential underreporting over this period. Methods We determined the annual incidence of notified cases of measles – for each year – in northern, western, eastern and southern Germany and across the whole country. We then used measles-related health insurance claims to estimate the corresponding incidence. Findings In each year between 2007 and 2011, there were 6.9–19.6 (mean: 10.8) notified cases of measles per million population. Incidence decreased with age and showed geographical variation, with highest mean incidence – 20.3 cases per million – in southern Germany. Over the study period, incidence decreased by 10% (incidence rate ratio, IRR: 0.90; 95% confidence interval, CI: 0.85–0.95) per year in western Germany but increased by 77% (IRR: 1.77; 95% CI: 1.62–1.93) per year in eastern Germany. Although the estimated incidence of measles based on insurance claims showed similar trends, these estimates were 2.0- to 4.8-fold higher than the incidence of notified cases. Comparisons between the data sets indicated that the underreporting increased with age and was generally less in years when measles incidence was high than in low-incidence years. Conclusion Germany is still far from achieving measles elimination. There is substantial regional variation in measles epidemiology and, therefore, a need for region-specific interventions. Our analysis indicates underreporting in the routine surveillance system between 2007 and 2011, especially among adults.